Stakeholders Pressures and Strategic Prioritisation: An Empirical Analysis of Environmental Responses in Argentinean Firms - Vazquez-Brust, D. A. (Journal of business ethics, 2010)
This article focusses on corporate attitudes to stakeholder environmental pressures in Argentina. It uses a cross section survey of 505 CEOs of Argentinean firms to gather information on environmental attitudes and a stakeholder theory framework to design and interpret the statistical analyses. It is underpinned by theoretical and empirical findings in the literature on stakeholder management, targeting in particular studies that deal with corporate social responsibility (CSR) in Latin America. Its general aim is to gain a deeper empirical understanding of the coherence between managers’ perceptions of stakeholder pressures and the importance they are given in corporate CSR strategies through an empirical investigation of environmental management (EM) decisions. In doing so, it uncovers general differences in the way firms perceive and treat groups of stakeholders. It also detects variations across firms, observing that some are typically proactive in their response to stakeholder pressures whilst others are less responsive. Profiling the various stakeholder networks and the corporate response strategies in this way encourages the development of stakeholder-focussed policies and corporate strategies that emphasise communications, awareness and a clear sense of direction. It concludes that CSR appears to be more effective in the protection of the environment than previously reported. Although this study focusses on EM in Argentina, the findings are more generally applicable.